Carers Extrinsic Disorder: Dementia & Alzheimers - Thomson, Wendy (British Journal of Healthcare and Medical Research, 2024)
This article makes the case for a new diagnosis: Carers Extrinsic Disorder, caused by the extrinsic determinants of carers of patients with dementia &Alzheimers. It argues that the causal symptoms are beyond the control of the carer. It further attempts to high light the role of the carer as the disease in the patient escalates - from imperceptible signs and symptoms to full blown diagnosed dementia. The carer becomes the lone interface between the deteriorating patient, society, and the provision of the often-disunited welfare systems. A biopsychophysical role undertaken often by a spouse without any previous medical, therapeutic training or experience.